Electrical equipment transfomers, breakers and switches - Primedia Workplace Learning ([United States] : PRIMEDIA Workplace Learning)
This interactive training unit is designed to familiarize trainees with the operation of transformers, circuit breakers, and various types of switches. After completing this unit, trainees should be able to explain the principles of transformer operation, identify some of the basic components of a transformer, and describe checks that are generally made during a transformer inspection. They should also be able to describe the general operation of a circuit breaker, explain how to reset a tripped circuit breaker and rack out a circuit breaker, and describe the basic operation of pushbutton switches and rotary switches.
Keywords: Electric power systems control; Electricity